Caffeine prevents high-intensity exercise-induced increase in enzymatic antioxidant and Na+-K+-ATPase activities and reduction of anxiolytic like-behaviour in rats. (2nd November 2017) - Vieira, Juliano M.; Carvalho, Fabiano B.; Gutierres, Jessié M.; Soares, Mayara S. P.; Oliveira, Pathise S.; Rubin, Maribel A.; Morsch, Vera M.; Schetinger, Maria Rosa; Spanevello, Roselia M.
ABSTRACT: Objective: Here we investigated the impact of chronic high-intensity interval training (HIIT) and caffeine consumption on the activities of Na + -K + -ATPase and enzymes of the antioxidant system, as well as anxiolytic-like behaviour in the rat brain. Methods: Animals were divided into groups: control, caffeine (4 mg/kg), caffeine (8 mg/kg), HIIT, HIIT plus caffeine (4 mg/kg) and HIIT plus caffeine (8 mg/kg). Rats were trained three times per week for 6 weeks, and caffeine was administered 30 minutes before training. We assessed the anxiolytic-like behaviour, Na + -K + -ATPase, superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) activities, levels of reduced glutathione (GSH) and thiobarbituric acid reactive substances (TBARS) in the brain. Results and discussion: HIIT-induced anxiolytic-like behaviour increased Na + -K + -ATPase and GPx activities and TBARS levels, altered the activities of SOD and CAT in different brain regions, and decreased GSH levels. Caffeine, however, elicited anxiogenic-like behaviour and blocked HIIT effects. The combination of caffeine and HIIT prevented the increase in SOD activity in the cerebral cortex and GPx activity in three brain regions. Our results show that caffeine promoted anxiogenic behaviour and prevented HIIT-induced changes in the antioxidant system and Na + -K + -ATPase activities.